Legal problems of balancing public and private interests in the field of natural resources usage - Shakhray, Irina S. (Journal of the Belarusian State University. Law, 2020)
The article analyses the features of the correlation of public and private interests in the field of natural resources usage and general approaches to ensuring their balance. The importance of harmonizing the entire spectrum of interests (economic, environmental, social and others), determining their priority and expressing these priorities in environmental (natural resource) law and legislation is substantiated. The conclusion is drawn on the advisability of developing legal mechanisms within which the search for a balance of interests is ensured not only by the state authorities imperatively, but also with the direct participation of other subjects of natural resource relations.